(untitled) (British Journal of Global Ecology and Sustainable Development, 2024)
This research is a development research aimed at producing valid, practical and effective student Mathematics Worksheets based on a holistic approach. Worksheets based on a holistic approach are learning tools in the form of worksheets that contain information for carrying out scientific activities based on a holistic approach for students. The development stages follow the 4-D model with the stages of defining, planning and developing. Based on the expert’s assessment of the mathematics worksheet based on a holistic approach using an internal consistency test, the Gregory test device has a valid profile with strong internal consistency in each aspect. Expert judgment is based on format 4.8, language 3.8, for content 4.8 and illustrations obtained 4.7, categorized with an average validation result of 4.53 which is categorized as very valid. The results of limited trials of the developed worksheets were found to have a practical profile with a percentage of 100% implementation of the device. and declared effective with an average student performance score for worksheets an average of 89.5 out of a maximum value of 100, the time for working on worksheets all met the specified criteria limit of 81%. And 86% gave a positive response to the worksheets that were tested. It was concluded that the worksheet has a valid, practical and effective profile. It is expected that the quality of students’ mathematics education can be improved by using student mathematics worksheets based on a holistic approach.